Formation of disulfide bridges drives oligomerization, membrane pore formation, and translocation of fibroblast growth factor 2 to cell surfaces - Müller, Hans-Michael; Steringer, Julia P.; Wegehingel, Sabine; Münster, Maximilian; Dimou, Eleni; Unger, Sebastian; Weidmann, Georg; Andreas, Helena; Wild, Klemens; Sinning, Irmgard; Nickel, Walter (The journal of biological chemistry, 2015)
Fibroblast growth factor 2 (FGF2) is a key signaling molecule in tumor-induced angiogenesis. FGF2 is secreted by an unconventional secretory mechanism that involves phosphatidylinositol 4,5-bisphosphate-dependent insertion of FGF2 oligomers into the plasma membrane. This process is regulated by Tec kinase-mediated tyrosine phosphorylation of FGF2. Molecular interactions driving FGF2 monomers into membrane-inserted FGF2 oligomers are unknown. Here we identify two surface cysteines that are critical for efficient unconventional secretion of FGF2. They represent unique features of FGF2 as they are absent from all signal-peptide-containing members of the FGF protein family. We show that phosphatidylinositol 4,5-bisphosphate-dependent FGF2 oligomerization concomitant with the generation of membrane pores depends on FGF2 surface cysteines as either chemical alkylation or substitution with alanines impairs these processes. We further demonstrate that the FGF2 variant forms lacking the two surface cysteines are not secreted from cells. These findings were corroborated by experiments redirecting a signal-peptide-containing FGF family member from the endoplasmic reticulum/Golgi-dependent secretory pathway into the unconventional secretory pathway of FGF2. Cis elements known to be required for unconventional secretion of FGF2, including the two surface cysteines, were transplanted into a variant form of FGF4 without signal peptide. The resulting FGF4/2 hybrid protein was secreted by unconventional means. We propose that the formation of disulfide bridges drives membrane insertion of FGF2 oligomers as intermediates in unconventional secretion of FGF2.